Practical LEGO Technics Bring Your LEGO Creations to Life - Rollins, Mark.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
You already know you can create amazing things with LEGO, but did you know you can also make vehicles that roll and model plans that include landing gear and flaps that actually extend and retract? You can even make functional robots without getting into Mindstorms and programming. In Practical LEGO Technics, Mark Rollins shows you how to use LEGO and Power Functions components like motors and remote controls to create motorized cars, all terrain vehicles, vehicle steering, construction equipment such as cranes and forklifts, airplanes. All-in-all, you'll learn to create a wide variety of fun, unique LEGO creations. LEGO Technic is similar to Mindstorms in that you can create all sorts of cool vehicles and gadgets. But unlike Mindstorms, you don't have to learn programming. Power Functions allows you to add motors, remote control, and battery boxes to your LEGO projects, no programming required. And while you could just build a LEGO Technic gadget from a boxed set, with Practical LEGO Technics, you'll learn the hows and whys of Technic project design, and pick up ideas for your own custom projects. Please note: The print version of this title is in black & white; the ebook is full color. You can download color images from the book at http://www.apress.com/9781430246114 Covers basic design for motorized vehicles that run and steer. Shows how to build headlights and more using the Power Functions Light Kit. Provides suspension design for use in building all-terrain vehicles. Helps you build construction equipment, including a crane and forklift.
Keywords: Computer input-output equipment; Computer hardware; Hardware and Maker; Computer Hardware